A crowdsourcing design framework for concept generation. Issue 1 (2016) - Liu, Ang; Lu, Stephen C.-Y.
Abstract: In the Internet era, customers become increasingly used to publishing their reviews of products online. This paper presents a crowdsourcing design framework (CDF) that exploits those online customer reviews to support concept generation in conceptual design. CDF guides designers through a systemic qualitative data analysis process to abstract relevant design intelligence based on highlighted customer reviews published by lead users, towards a database of logic propositions, which is queried by designers to increase knowledge and inspire creativity. A controlled experiment shows that CDF significantly enhances novice designers' ideation effectiveness and improves their innovative design thinking.